Investigating the Suitability of Selected Structural Material for the Blade of an Horizontal Axis Wind Turbine - M. Shuwa; G. M. Ngala; A. M. El-jummah (Arid Zone Journal of Engineering, Technology and Environment, 2017)
This work presents a comparative analysis on the structural material of a blade used for the horizontal axis wind turbine, which was based on previously developed blade geometry. Two blades of the same parameter: 0.25 m chord lengths at 8 o angle of attack, but different structural materials were compared. This to identify an optimized blade structural material in terms of locally available, strength, cost effectiveness and environmental safety that will be suitable for Maiduguri’s weather condition. The ultimate flap - and edge - wise deflections and load conditions under minimum blade mass (6.8 kg) are determined. These investigations were carried out in two stages: predictions of the aerodynamic analysis using Computational Fluid Dynamics (CFD) code (ANSYS Fluent CFD commercial tool) with Blade Element Momentum (BEM) theory, Finite Element Method (FEM) coded in MATLAB software for the structural analysis and experimental evaluations for the purpose of validation of predicted data obtained. These were employed in order to provide sufficient conclusions of the aerodynamic and structural data that will provide better performance of the blade. These data are expected to handle the design variables meant for the optimization of the blade based on the selected structural material. The blades of each material were divided into 15 elements along the blade span with each element assumed to have uniform cross sectional area. Pressure distribution within the computational domain and around the airfoil section in two dimensions (2D) was predicted. The validated results of the load to deflection showed good agreement and that each of the blade material were based on the structural strength. From the result obtained, it shows that the aluminium blade structure material has good reliability with better performance. These were significant between the maximum strength and the minimum blade mass for aerodynamic loadings, hence better blade structure than that developed from beach wood and most suitable under an ultimate wind speed of 30 m/s.